2020
DOI: 10.1093/annweh/wxaa091
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Skin Disease in Physicians: A Review of the Literature

Abstract: Objectives Occupational skin disease (OSD) arises from work-related activity. However, there is a paucity of literature on OSD in physicians. The aim of the this review was therefore to examine and summarize what types of symptomatic OSD physicians experience. Methods We conducted a systematic literature search on Cochrane Library, Embase, and Pubmed. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In a study from Denmark, NRL allergy was diagnosed in 2.5% of HCWs with hand eczema, 37 but in a similar Australian population the prevalence of NRL allergy was as much as 13% 36 . A recent systematic review on OSDs in physicians showed the prevalence of NRL allergy within 2.4% to 14.9% 39 . Such differences in the prevalence of NRL allergy in HCWs are probably due to the varying extent of implemented preventive measures regarding NRL allergy in different countries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a study from Denmark, NRL allergy was diagnosed in 2.5% of HCWs with hand eczema, 37 but in a similar Australian population the prevalence of NRL allergy was as much as 13% 36 . A recent systematic review on OSDs in physicians showed the prevalence of NRL allergy within 2.4% to 14.9% 39 . Such differences in the prevalence of NRL allergy in HCWs are probably due to the varying extent of implemented preventive measures regarding NRL allergy in different countries.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently found occupational contact allergy in HCWs with OSDs was to rubber additives in medical gloves (thiurams, diphenylguanidine), preservatives (formaldehyde, isothiazolinones), and disinfectants (glutaraldehyde). 36 , 38 , 39 It seems that the development of allergic contact dermatitis due to occupational allergens during apprenticeship is not common in nurses. In contrast to this, the development of irritative contact dermatitis seems common in this population, keeping in mind high proportions of self‐reported hand eczema in this population in our study and studies from Germany and the Netherlands (31%‐46%), 26 , 27 in contrast to HCWs who reported hand eczema prevalence at around 20%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FA contact allergy may also be the result of exposure to FRs that are widely used, not only in cosmetics, but also in occupational products, such as metalworking fluids, 16,30 cleaning agents, and disinfectants. Occupations at risk for occupational ACD from FA/FRs comprise, among others, metalworkers, health care workers (eg, hemodialysis nurses, laboratory technicians, embalmers), hairdressers and beauticians, painters, veterinary and dental students, and laborers in the food‐processing industry 3,24,30‐33 …”
Section: Prevalence Of Sensitizationmentioning
confidence: 99%